Copyright Protection in NFT Transactions Involving Blockchain-Based Digital Assets - Ade Lukman Firmansyah; Aldo Delano; Khoirul Tamam; Fenny Fatriany (Journal of Human Interaction and Social Studies, 2026)
The rapid expansion of blockchain technology and the emergence of Non-Fungible Tokens (NFTs) have transformed digital ownership models and generated significant challenges for contemporary copyright law. This study examines the legal relationship between NFT ownership and copyright protection, analyzes the legal issues arising from blockchain-based digital asset transactions, and evaluates the regulatory implications for Indonesia. Employing a normative legal research design with conceptual, comparative, and doctrinal approaches, the study analyzes statutory regulations, legal doctrines, and scholarly literature concerning NFTs, blockchain governance, and intellectual property rights. The findings indicate that NFT ownership does not automatically transfer copyright ownership of the underlying digital work, creating substantial legal uncertainty regarding licensing, royalty distribution, authorship recognition, and rights enforcement. Although blockchain technology offers innovative mechanisms for authentication, traceability, and automated royalty management through smart contracts, these technological features remain insufficient to resolve fundamental legal questions concerning copyright ownership and infringement. The study further identifies regulatory gaps within Indonesia’s existing legal framework, particularly the inability of current copyright and digital transaction regulations to adequately address decentralized digital asset ecosystems. The research recommends regulatory reform focused on clarifying ownership rights, strengthening copyright protection mechanisms, and developing adaptive governance frameworks capable of accommodating technological innovation while ensuring legal certainty.